Evaluation of the Use of POSSUM and P-POSSUM Score as a Tool for Prediction of Surgical Outcome (Journal of Surgical Sciences, 2019)
Background: There are many scoring systems that predict the risk of mortality with varyingdegrees of accuracy. The ideal scoring system for surgical outcome should be quick andeasy to use and should be applicable to all general surgical procedures. POSSUM(Physiological and Operative Severity Score for enumeration of Mortality and Morbidity) andP-POSSUM (Portsmouth POSSUM) are the most appropriate scoring systems currentlyavailable in general surgery to predict thirty days mortality and morbidity.Objective: The study was done to assess the value of POSSUM in predicting the morbidityrate and the value of P-POSSUM in predicting the mortality rate in general surgical patientsof our country.Methods: Aprospective study was performed in 120 general surgical patient. The risks ofmorbidity and mortality were calculated by using the POSSUM equation for morbidity andthe P-POSSUM equation for mortality in each patient. The predicted risks were comparedwith the observed risks of morbidity and mortality for 30 days after surgery and statisticallyanalysed.Results: The difference in p value of predicted risk of morbidity by POSSUM equation andobserved morbidity; calculated by chi square test(x2 =1.36, d.f=4,p=0.24,0/P ratio was1.18); which was not statistically significant. The predicted mortality by P-POSSUM equationand observed mortality; calculated by Fisher's exact test(p=1) was not found statisticallysignificant. The Pearson correlation has shown significant correlation at the 0.01 level (2tailed) for the observed and predicted mortality and morbidity(r=O. 701).ROC analysesshowed both POSSUM and P-POSSUM scores to be good predictors of 30-day morbidity andmortality with area under the curve values (AUC) of 0.887 and 0.991 respectively.ConclusionPOSSUM and P-POSSUM can be used as a valid tool for using risk prediction of morbidityand mortality in our set up.Journal of Surgical Sciences (2017) Vol. 21 (1) :11-14